Desempenho de dois espectrofotômetros na avaliação das alterações de cor de lesões cariosas não cavitadas em esmalte - Vieira, Flávia Isaia (2015)
The aim of this study was evaluate the performance of two spectrophotometer devices in assessing color changes of dental enamel after artificial caries induction (demineralization) and treatment with fluorides. The Easyshade spectrophotometer (VITA, Germany) and SP60 (Ex-Rite, USA) were used to measure the color changes of 30 bovine enamel blocks (n=10) in evaluation times: initial (sound enamel) (T0), demineralized enamel (T1 after pH cycling) and after treatment with fluoride agents 5 applications of fluoride gel (2% sodium fluoride group NaF and 1.23% acidulated phosphate fluoride APF group) (T2 to T6). The specimes in control group were kept in deionized water during the experimental time and received no treatment with fluoride. Obtained color change values (ΔE) as well as the values of each CIE L*a*b* dimensions were subjected to ANOVA and Tukey s post hoc test (α=0,05). The Pearson s correlation coefficient was used to measure a correlation study between the two devices. Results showed tha SP60 device was able on identifying and monitoring enamel color changes (p=0.000) and CIE L*a*b* dimension on evaluation times (p=0.000). On other hand, Easyshade showed no significant differences in main factors evaluation time (p=0.713) and treatment (p=0.684). Low correlation between the two devices was observed (r=0.25; p= 0. 001). Based on the obtained results, one can conclude that spectrophotometer SP60 was able to identify enamel color changes during enamel de-remineralization. Color changes in enamel were not assessed by Easyshade device.